The Relationship Between Socio-Economic Status And Interest In Continuing Study Among Students At Sahid University Surakarta - riskiana, dhian; Khusnuliawati, Hardika (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This study aims to determine the relationship between socioeconomic status and interest in continuing college in students at Sahid University Surakarta. Someone who will continue their studies to college will consider various factors, including the socioeconomic status of the family and the college they are aiming for. This socioeconomic status can be seen from the family's educational background, occupation, and family income. The college referred to in this study is Sahid University Surakarta. This study uses a quantitative method with a correlational approach. The population in this study were all students at Sahid University Surakarta. The sample was taken using a proportional random sampling technique of 230 people. The results of this study indicate that there is a relationship between socioeconomic status and interest in continuing college. The higher the socioeconomic status, the higher the student's interest in college.